Scaffold Proteins Regulating Extracellular Regulated Kinase Function in Cardiac Hypertrophy and Disease - Liang, Yan; Sheikh, Farah (Frontiers in Pharmacology, 2016)
The mitogen activated protein kinase (MAPK)-extracellular regulated kinase 1/2 (ERK1/2) pathway is a central downstream signaling pathway that is activated in cardiac muscle cells during mechanical and agonist-mediated hypertrophy. Studies in genetic mouse models deficient in ERK-associated MAPK components pathway have further reinforced a direct role for this pathway in stress-induced cardiac hypertrophy and disease. However, more recent studies have highlighted that these signaling pathways may exert their regulatory functions in a more compartmentalized manner in cardiac muscle. Emerging data has uncovered specific MAPK scaffolding proteins that tether MAPK/ERK signaling specifically at the sarcomere and plasma membrane in cardiac muscle and show that deficiencies in these scaffolding proteins alter ERK activity and phosphorylation, which are then critical in altering the cardiac myocyte response to stress-induced hypertrophy and disease progression. In this review, we provide insights on ERK-associated scaffolding proteins regulating cardiac myofilament function and their impact on cardiac hypertrophy and disease.